Pengaruh Merger Dan Akuisisi Serta Kinerja Keuangan Terhadap Nilai Perusahaan Melalui Kebijakan Dividen Sebagai Variabel Intervening Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Vahra Oktaladisa; Elfiswandi; Putri Intan Permata Sari (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the influence of Mergers and Acquisitions, Financial Performance, and Dividend Policy as an intervening variable on company value for banking companies listed on the Indonesia Stock Exchange from 2020-2024. The sample was determined using the purposive sampling method, resulting in companies that met the research criteria. The data analysis methods used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, hypothesis testing, and path analysis testing. The research results indicate that mergers and acquisitions and financial performance significantly influence dividend policy. Additionally, financial performance and dividend policy also significantly impact company value. However, mergers and acquisitions do not significantly affect company value. Furthermore, the analysis results show that mergers and acquisitions and financial performance significantly influence company value thru dividend policy.